PENGARUH ROTASI KANTOR AKUNTAN PUBLIK (KAP), TENURE AUDIT DAN UKURAN KAP TERHADAP KUALITAS AUDIT - Faisal, Muhammad (UNIB Press, 2019)
Accounting is a form of accountability and conveying financial information of a company or organization to parties concerned. However, the accounting report could potentially be affected by private interests, while the users of financial reports are very concerned to receive reliable financial reports. Therefore there is a need for an independent third party to mediate the two parties (agent and principal) with different interests. The independent party is an auditor who is responsible to provide assessment and opinion statement on the fairness of the financial report presented. DeAngelo (1981) defines audit quality as